Construction Cost Estimation Model For Airport Construction - Inayatullah Inayatullah; Leksmono Suryo Putranto; Dadang M. Ma'soem (Journal of Social Research, 2025)
The development of air transportation infrastructure, especially airports, plays an important role in improving connectivity, mobility, and economic and social growth. Estimating construction costs is an essential step in the development planning process to ensure proper budget allocation. This study aims to develop a special construction cost estimation model for airport construction by analyzing various variables that affect costs. The research uses a quantitative approach with primary data obtained from airport building construction work contracts and interviews with professional practitioners in this field. Sample data was taken from 22 output reports of airport construction work packages that have been completed or are being planned in several provinces in Indonesia. Data analysis techniques include correlation coefficient tests, determination, normality tests, multicollinearity tests, as well as t-tests and model variations. The results of the study are expected to produce an accurate, easy-to-use, and accountable cost estimation model, taking into account independent variables such as job characteristics, contract types, and market conditions. This estimation model is expected to be able to minimize the discrepancy between cost estimates and the realization of implementation costs, thereby contributing to the efficiency and sustainability of airport development. This research provides a scientific basis for decision-making related to the management of the construction budget for airport development in Indonesia.